80 Years of Business Cycle Studies at DIW Berlin (Editorial) - Alfred Steinherr (Vierteljahrshefte zur Wirtschaftsforschung, 2006)
To celebrate its 80th anniversary DIW Berlin organised on 8 and 9 December 2005 a conference centred on two themes. The first dealt with the methods and performance of forecasting. The second discussed scenarios for the future of Europe and its major economies. A selection of the contributions to the conference is presented in this volume. Section 2 is an overview of the papers in this volume. The following sections deal with the history of business cycle studies at DIW Berlin viewed from the wider perspective of the evolution of forecasting. To do that I first describe in Section 3 the historical context for setting up of the institute in 1925. Then I organize the discussion along the lines of the methods and tools of forecasting which I classify into three broad categories. The period 1925 to 1950 was marked by the search for laws of motion and supporting statistical evidence. This was followed by a period stretching from 1950 to 1990s, described in Section 4, during which statistical information was organized around the concepts of national income accounts and input-output tables. Equipped with well-organized statistics the construction of macroeconomic models, first of the national economy and later of the world economy were developed. The third phase picking up momentum in the 1990s, and discussed in Section 5, focussed more and more on the provision of timely data, raw and transformed, as market participants of a globalized economy, in particular financial markets, need on a daily - even hourly - basis information updates on their Bloomberg screens.
Keywords: 330; Wirtschaftsforschungsinstitut; Konjunkturforschung; Deutschland